2010
DOI: 10.1016/j.ejso.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Histology after lumpectomy in women with epithelial atypia on stereotactic vacuum-assisted breast biopsy

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. M A N U S C R I P T A C C E P T E D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…A study by Polat et al 16 reported a greater upstage rate for mixed ADH/ALH of 18% versus an upstage rate of 12% for ADH alone when analyzing samples from all core needle biopsies, including stereotactic, ultrasonography, and MRI guidance. Graesslin et al 17 showed an upstage rate of 28% for mixed ADH/ALH versus 18% for ADH alone in patients with breast biopsy with stereotactic guidance. A study by Hartmann et al 18 in 2014 showed a subsequent risk of breast cancer in patients with mixed ADH and ALH on core needle biopsy that was similar at 22% compared with an overall risk of 20% for ADH or ALH alone when these lesions are followed up.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Polat et al 16 reported a greater upstage rate for mixed ADH/ALH of 18% versus an upstage rate of 12% for ADH alone when analyzing samples from all core needle biopsies, including stereotactic, ultrasonography, and MRI guidance. Graesslin et al 17 showed an upstage rate of 28% for mixed ADH/ALH versus 18% for ADH alone in patients with breast biopsy with stereotactic guidance. A study by Hartmann et al 18 in 2014 showed a subsequent risk of breast cancer in patients with mixed ADH and ALH on core needle biopsy that was similar at 22% compared with an overall risk of 20% for ADH or ALH alone when these lesions are followed up.…”
Section: Discussionmentioning
confidence: 98%
“…Radiologic description of flat epithelial atypia is scant in the literature [14,15]. Flat epithelial atypia most often presents at diagnosis as microcalcifications [4,7,10,14,[16][17][18][19]. Our study shows that pure flat epithe-lial atypia presenting as microcalcifications lacks specific features.…”
Section: Discussionmentioning
confidence: 99%
“…Histological assessment may prove problematic given the known interobserver variability in diagnosis of atypical epithelial proliferations. Immunohistochemistry for CK5/6 and oestrogen receptor may be of value in distinguishing between epithelial hyperplasia of usual type and atypia, especially when assessing the limited tissue samples obtained in needle core and vacuum-assisted biopsies 21. Immunohistochemistry for E-cadherin may highlight small foci of LN22 and may also help distinguish LN from areas of artefactual dyscohesion.…”
Section: Discussionmentioning
confidence: 99%